2019
DOI: 10.1186/s13063-019-3195-9
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid autotransplantation at a novel site for better evaluation of the grafted gland function: study protocol for a prospective, randomized controlled trial

Abstract: BackgroundHypoparathyroidism is one of the most common complications encountered in thyroidectomy. In addition to parathyroid in-situ preservation, parathyroid autotransplantation (PA) is another important remedial method for patients whose parathyroid glands have been removed. However, an accurate evaluation method for the function of a transplanted parathyroid is lacking. Our preliminary study indicated that patients with PA at novel sites near antecubital veins had higher serum concentrations of parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For patients with hoarseness, an indirect laryngoscopy was programmed at 1, 3 and 6 months postoperatively, respectively, until the vocal cords function. After 6 months recurrent paralysis is considered permanent [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…For patients with hoarseness, an indirect laryngoscopy was programmed at 1, 3 and 6 months postoperatively, respectively, until the vocal cords function. After 6 months recurrent paralysis is considered permanent [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…( 31 ) confirmed the survival of transplanted parathyroid glands by subcutaneous transplantation of parathyroid glands in the forearm and observed that serum parathyroid hormone levels were two to three times higher on the transplanted side than on the non-transplanted side. A prospective study compared postoperative parathyroid hormone concentrations in transplanted and non-transplanted forearms by injection at a new subcutaneous site close to the cephalic arm vein to provide a more precise method to confirm the success of parathyroid transplantation ( 32 ). The author believes that the simplest, most direct, and effective way to determine whether a transplanted parathyroid gland is viable is to determine whether PTH concentrations in the reflux venous blood at the transplanted parathyroid gland are higher than those in the venous blood of the body circulation; this would demonstrate the presence of a source of parathyroid hormone secretion at the transplantation site.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, parathyroid function after thyroid surgery is evaluated using clinical symptoms and serum PTH and calcium concentrations ( 33 ). In previous studies, the sternocleidomastoid muscle was selected as the graft site to avoid making a second surgical incision; however, this method precludes differentiating parathyroid function in the transplantation site and the preserved parathyroid glands ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%